In vitro co-culture models for the assessment of orthopedic antibacterial biomaterials - Eijkel, Benedictus I. M.; Apachitei, Iulian; Fratila-Apachitei, Lidy E.; Zadpoor, Amir A. (Frontiers in Bioengineering and Biotechnology, 2024)
The antibacterial biofunctionality of bone implants is essential for the prevention and treatment of implant-associated infections (IAI). In vitro co-culture models are utilized to assess this and study bacteria-host cell interactions at the implant interface, aiding our understanding of biomaterial and the immune response against IAI without impeding the peri-implant bone tissue regeneration. This paper reviews existing coculture models together with their characteristics, results, and clinical relevance. A total of 36 studies were found involving in vitro co-culture models between bacteria and osteogenic or immune cells at the interface with orthopedic antibacterial biomaterials. Most studies (~ 67 %) involved co-culture models of osteogenic cells and bacteria (osteo-bac), while 33 % were co-culture models of immune cells and bacterial cells (im-bac). All models involve direct co-culture of two different cell types. The cell seeding sequence (simultaneous, bacteria-first, and cells-first) was used to mimic clinically relevant conditions and showed the greatest effect on the outcome for both types of co-culture models. The im-bac models are considered more relevant for early peri-implant infections, whereas the osteo-bac models suit late infections. The limitations of the current models and future directions to develop more relevant coculture models to address specific research questions are also discussed.